Properties Enhancement of Cu2O/TiO2 Heterostructure Film Using Two-step Hydrothermal and Potentiostatic Deposition Method - Farizaa, M.; Norazlinab, A.; Azman, T.; Ahmada, M. K.; Murakami, K. (2024)
Two-steps hydrothermal were demonstrated to create a high efficiently interfacial layer of TiO2 thin film. The first hydrothermal was conducted to synthesize a well-aligned and compact structure of TiO2 nanorods on FTO substrate. Etching treatment in an acidic medium of hydrochloric acid (HCI) as a second hydrothermal favors increasing the surface area prior to any deposition to be a heterostructure film. The morphology of nanorods changed while the electrical resistivity decreased, demonstrating that the etching treatment had a substantial effect on the TiO2 thin film properties. Cyclic voltammetry (CV) was conducted prior deposition. The electrodeposition of Cu20 on the TiO2 thin film was fabricated by using copper acetate-based solution with pH value of 12.0 at bath temperature of 60°C. The finding revealed that the pyramidal structure of Cu20 film was deposited uniformly, which is believed that the properties of TiO2 interfacial layer were excellently improved.